Integrating Local Wisdom in Religious Moderation Education: A Study of Mountain Slope Communities - Zubaidi, Ahmad; Jali, Hasan (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
The slopes of Mount Bromo in Probolinggo represent a multicultural society grappling with the implementation of religious moderation. The area's distinct geographical and cultural context necessitates a localized approach by integrating local wisdom. This study explores how local traditions foster religious moderation using Peter L. Berger’s theory of social construction-externalization, objectivation, and internalization. A qualitative method was employed, with data collected through interviews, observations, and documentation. Findings indicate that local wisdom is externalized through cultural practices promoting tolerance, such as gotong royong, and joint religious-cultural ceremonies like Kasada and Melasti. These expressions become objectified as shared rituals and social symbols. These values are internalized through informal education and community socialization, shaping individual and communal attitudes. Integrating local wisdom into religious moderation fosters an inclusive identity, reduces interfaith tensions, and promotes lasting harmony in this diverse society. Viewed through Berger's framework, the process successfully creates sustainable social cohesion. This study concludes that contextualizing religious education through local traditions effectively strengthens multicultural resilience and nurtures peaceful coexistence in rural settings like Mount Bromo.